Avaliação do consumo alimentar e percepção da imagem corporal de culturistas - Paula, Bianca Baptista de; Sarrassini, Felicia Bighetti; Tonello, Maria Georgina Marques; Neiva, Cassiano Merussi [UNESP]; Manochio, Marina Garcia (My University, 2014)
In bodybuilding, sport that emerged in Brazil in the 70s, competitors are judged by physical appearance, size and muscle definition. The present study aimed to assess dietary intake, supplement use, and it also investigated body image perceptions of bodybuilders. Practitioners of three different gyms in the state of São Paulo participated in the study. They filled the anamnesis form containing data on food consumption and intake of supplements and also answered a questionnaire on the perception of body image (Satisfaction Scale with Body Appearance). The study showed a considerable food inadequacy with an average of carbohydrate intake of 41.84% ± 10.88%, of lipid, an average of 18.96% ± 6.40% and of protein 39.20% ± 10.41%. In pre-competition, the average of daily carbohydrate intake is reduced to 22.69% ± 12.34%, the lipid increases to 25.68% ± 14.0% and the protein increases to 51.63% ± 10.28%. It was observed that all individuals take some sort of supplement. Considering the perception of body image 60% of the appraised are fully satisfied with the muscular appearance and 40% has greater risk of developing vigorexia. As the bodybuilder has rigid dietary control, it is important nutritional monitoring. So it is necessary a better identification and guidance of risk groups for the development of body image disturbances through specialized professionals such as dieticians, psychologists and coaches for success training, aiming at physical and mental well being of the athletes.

O culturismo, esporte no qual os competidores são julgados pela aparência física, tamanho e definição muscular, surgiu no Brasil na década de 70. O presente estudo teve como objetivo avaliar o consumo alimentar, uso de suplementos e investigou a percepção da imagem corporal de culturistas. Participaram deste estudo, praticantes de três diferentes academias do estado de São Paulo, os quais preencheram a ficha de anamnese contendo dados sobre consumo alimentar e ingestão de suplementos e o questionário para investigar a percepção da imagem corporal (Escala de Satisfação com a Aparência Corporal). O estudo mostrou grande inadequação alimentar com média de ingestão de carboidratos de 41,84% ± 10,88%, de lipídeos em média 18,96% ± 6,40% e em relação à proteína 39,20% ± 10,41%. Já em fase de pré-competição a média diária de ingestão de carboidrato se reduz para 22,69% ± 12,34%, a de lipídio aumenta para 25,68% ±14,0% e a proteína aumenta para 51,63%± 10,28%. Observou-se que todos os indivíduos consomem algum tipo de suplemento alimentar. Quanto à percepção da imagem corporal 60% dos avaliados estão totalmente satisfeitos com a aparência muscular e 40% tem maiores riscos de desenvolver a vigorexia. O culturista possui controle dietético rígido, assim, é importante um acompanhamento nutricional, portanto faz-se necessário melhor identificação e orientação de grupos de riscos para o desenvolvimento de distúrbios na imagem corporal, através de profissionais especializados como nutricionistas, psicólogos e treinadores para o sucesso do treinamento, visando o bem estar físico e mental dos atletas.
Evaluation of food consumption and body image perception of bodybuilders
Evaluación del consumo alimenticio y la percepción corporal de fisicoculturistas
Keywords: Athletes; Food intake; Body; Atletas; Ingestão alimentar; Imagem corporal